PENGARUH KUALITAS PELAYANAN DAN KEUNGGULAN PRODUK iB HASANAH TERHADAP KEPUASAN NASABAH PADA PT BANK BNI SYARIAH MALANG - Dyah Mustika Rini; M. Hufron; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACT This study aims to: (1) identify and analyze direct evidence variables, reliability, responsiveness, assurance, empathy and the advantages of the iB Hasanah Savings product simultaneously affect customer satisfaction at PT Bank BNI Syariah Malang, (2) Know and analyze the evidence variables. direct, reliability, responsiveness, assurance, empathy partially affect customer satisfaction at PT Bank BNI Syariah Malang, (3) Know and analyze how the advantages of iB Hasanah Savings products partially affect customer satisfaction at PT Bank BNI Syariah Malang. Population and sample of customers of PT Bank BNI Syariah Malang, amounting to 100 customers. Collecting data using a questionnaire. By using multiple linear regression analysis method. The results of this study indicate that: (1) The variables of direct evidence, reliability, responsiveness, assurance, empathy and superiority of the iB Hasanah Savings product simultaneously affect customer satisfaction at PT Bank BNI Syariah Malang. (2) The variables of direct evidence, reliability, responsiveness, assurance, empathy partially affect customer satisfaction at PT Bank BNI Syariah Malang. (3) the superiority of the iB Hasanah Savings product has a partial effect on customer satisfaction at PT Bank BNI Syariah Malang. Keywords        : Service Quality, Product Excellence and Customer Satisfaction.